2015
DOI: 10.13080/z-a.2015.102.007
|View full text |Cite
|
Sign up to set email alerts
|

Sulčių spaudimas iš sušaldytų/atšildytų mėlynių taikant impulsinio elektrinio lauko metodą

Abstract: Pulsed electric field is an efficient method for cell membrane permeabilization of food tissues with most research being done on fresh plant cells. Freeze/thawing is also known to be capable of cell membrane permeabilization. In this work, frozen/thawed European blueberry (Vaccinium myrtillus L.) fruits were treated with pulsed electric field in order to further enhance the cell membrane permeabilization and, hence, the quality of blueberry juice during the subsequent pressing process. Blueberries tissues were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…This was also observed in other juices, such as grape (Puértolas, Saldaña, Condón, Álvarez, & Raso, ), vegetable, and tomato juice (Vallverdú‐Queralt et al, ) where authors noticed higher contents of hydroxycinnamic acids and flavanones, while flavonols, coumaric, and ferulic acid remained unaffected by processing. When blueberries were exposed to PEF (1–5 kV/cm, 20 µs monopolar) prior pressing to juice ( p = 1.32), that increased polyphenolic and anthocyanins contents for 8.0% and 8.3%, respectively and enhanced antioxidant activity by 16.7% (Lamanauskas et al, ). Similarly, it was reported that after PEF (2 kV/cm, 1 µs), blueberries had 10% more anthocyanins and 25% polyphenolic compounds (Yu et al, ).…”
Section: Nutritional Propertiesmentioning
confidence: 99%
“…This was also observed in other juices, such as grape (Puértolas, Saldaña, Condón, Álvarez, & Raso, ), vegetable, and tomato juice (Vallverdú‐Queralt et al, ) where authors noticed higher contents of hydroxycinnamic acids and flavanones, while flavonols, coumaric, and ferulic acid remained unaffected by processing. When blueberries were exposed to PEF (1–5 kV/cm, 20 µs monopolar) prior pressing to juice ( p = 1.32), that increased polyphenolic and anthocyanins contents for 8.0% and 8.3%, respectively and enhanced antioxidant activity by 16.7% (Lamanauskas et al, ). Similarly, it was reported that after PEF (2 kV/cm, 1 µs), blueberries had 10% more anthocyanins and 25% polyphenolic compounds (Yu et al, ).…”
Section: Nutritional Propertiesmentioning
confidence: 99%
“…PEF pre‐treatment (3 kV/cm, 1.25 ms) was used to recover phenolics from apple pomace, sorghum flour, frozen European blueberries (1 kV/cm, 10 kJ/kg) (Lamanauskas et al, 2015). Red apples, mango, and papaya peels were examined to extract the polyphenols after PEF pre‐treatment.…”
Section: Results: Recovery Of Biomoleculesmentioning
confidence: 99%
“…Results showed that there was an insignificant difference between the control groups and the PEF treated apple juice [16]. Lamanauskas et al [17] reported that the application of PEF treatment (5 kV/cm) to blueberries resulted in enhanced antioxidant activity (up to +16.7%). More recently, Rodriguez-Roque et al [18] also observed an improved antioxidant capacity (up to +12.9%) of PEF treated (35 kV/cm, 1800 μs) fruit juice-based beverages compared to thermal processing (90°C, 60 s).…”
Section: Antioxidant Assaymentioning
confidence: 98%